Teacher of Special Education and teaching- learning process of students with autism - Andréa R. dos S. Boettger Giardinetto; Ana Carla Lourenço; Vera Lucia M. Fialho Capellini (Universidade Federal de Santa Maria (UFSM), 2013)
This paper has as subject autism, and sought to verify how the process of teaching and learning of students with autism occurs in a special education school. The Infantile Autism is today sorted as one of the "Global Developmental Disorders (PDD)" and is characterized by a severe and global impairment in several areas of development, such as reciprocal social interaction skills, communication skills and presence of stereotypic behavior, interests and activities. This study aimed to identify the teaching methodology used with adolescents with autism in special education and see in what ways this methodology assists in the teaching and learning of these students. To this end, participated in this study a teacher, expert in this issue, and three students with autism in a Special Education School located within the State of São Paulo. For data collection, 19 observations of activities performed by students with autism in the classroom were conducted and a semi-structured interview with the specialized teacher was applied. The results revealed that the teacher mentioned above does not use any specific teaching methodology to assist in the teaching and learning of these students, although there are some specific methodologies for individuals with autism, which are used in special education schools. Thus, there is a gap in the teaching process on the part of the teacher and an uncertainty about the learning process of these students with autism in this institution.